Effect of different inoculations on biogas and methane production through anaerobia biodigeston using residues from the avícola sector - Bortolini, Joseane; Silva, Ana Claudia Guedes; Tavares, Maria Hermínia Ferreira; Freitag, Dayane Taine; Fleck, Leandro; Kuczman, Osvaldo (Ciência e Natura, 2022)
The present study aimed to analyze the use of different digestates as inocula for the anaerobic digestion of poultry litter, evaluating the biogas and methane production. The inocula used were: bovine and porcine biofertilizer; with feeding loads of 0.67, 1.00 and 1.67 gVS L-1 day-1. Statistical analyses followed a split-plot design, where the main plot being inoculum and the feeding load as secondary. The experimental data were submitted to analysis of variance, at the level of 5% of significance. The following variable responses were considered: biogas production, specific biogas production as a function of volatile solids (VS) added to the biodigester, specific biogas production as a function of organic load, in terms of COD, and methane production. The highest rates of average biogas production, specific biogas production by VS added, specific production of biogas as a function of COD, and average methane production occurred with the use of bovine inoculum. Through the analysis of the total average percentage of methane production, productions of 63.0% and 54.5% for bovine and swine inoculum. Considering the results obtained, the use of bovine inoculum for the process of anaerobic digestion of poultry litter is recommended vinculado a produção de biogás e metano.